Integrated Physiological, Biochemical, and Molecular Analysis Identifies Important Traits and Mechanisms Associated with Differential Response of Rice Genotypes to Elevated Temperature - Sailaja, Boghireddy; Subrahmanyam, Desiraju; Neelamraju, Sarla; Vishnukiran, Turaga; Rao, Yadavalli Venkateswara; Vijayalakshmi, Pujarula; Voleti, Sitapati R.; Bhadana, Vijai P.; Mangrauthia, Satendra K. (Frontiers in Plant Science, 2015)
In changing climate, heat stress caused by high temperature poses a serious threat to rice cultivation. A multiple organizational analysis at physiological, biochemical and molecular level is required to fully understand the impact of elevated temperature in rice. This study was aimed at deciphering the elevated temperature response in eleven popular and mega rice cultivars widely grown in India. Physiological and biochemical traits specifically membrane thermostability (MTS), antioxidants, and photosynthesis were studied at vegetative and reproductive phases which were used to establish a correlation with grain yield under stress. Several useful traits in different genotypes were identified which will be important resource to develop high temperature tolerant rice cultivars. Interestingly, Nagina22 emerged as best performer in terms of yield as well as expression of physiological and biochemical traits at elevated temperature. It showed lesser relative injury, lesser reduction in chlorophyll content, increased super oxide dismutase, catalase and peroxidase activity, lesser reduction in net photosynthetic rate (PN), high transpiration rate (E) and other photosynthetic/ fluorescence parameters contributing to least reduction in spikelet fertility and grain yield at elevated temperature. Further, expression of 14 genes including heat shock transcription factors and heat shock proteins was analyzed in Nagina22 (tolerant) and Vandana (susceptible) at flowering phase, strengthening the fact that N22 performs better at molecular level also during elevated temperature. This study shows that elevated temperature response is complex and involves multiple biological processes which are needed to be characterized to address the challenges of future climate extreme conditions.